A resource-rich neighbor is a misfortune: The spatial distribution of the resource curse in Brazil - Phoebe W. Ishak (ZBW - Leibniz Information Centre for Economics, 2020)
We study the spatial distribution of the effect of oil and gas revenues on Brazilian municipalities, using variations in the international prices of oil and gas to establish causality. Oil and gas revenues increase economic activity, measured by night-time light emissions, in oil-producing municipalities but impose negative spill-overs on neighbouring municipalities. Spill-overs dominate beyond 150 km from oil activities and compensate direct effects in micro-regions. In oil municipalities, oil and gas revenues increase royalties, population, local real prices, crime, and real wages, essentially in manufacturing and services. Spillovers are negative on wages and prices and positive on royalties and crime.
Keywords: O11; O13; Q32; 330; Natural resources curse; oil; spill-over effects; Night-time lights; Brazil